Deep decarbonization in Germany: A macro-analysis of economic and political challenges of the 'Energiewende' (energy transition) - Claudia Kemfert; Petra Opitz; Thure Traber; Lars Handrich (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
[Introduction] With the goal of limiting the rise in global temperature to two degrees relative to preindustrial levels, the global community agreed to try to halve GHG emissions (vis-à-vis the level in 1990) by 2050. In order to achieve this ambitious target, developed countries ought to contribute profoundly to the reduction of GHG emissions by 80% to 95% in 2050 compared to their 1990 level. This requires coordinated efforts for a successful transition into a low-carbon economy. Against this backdrop, in the fall of 2013, the Deep Decarbonization Pathways Project (DDPP) was launched under the auspices of the UN Sustainable Development Solutions Network (SDSN). The project includes disaggregated pathway modeling exercises for twelve countries as well as complementary qualitative assessments of the countryspecific political settings and transformation strategies. Within this framework, this report contributes a qualitative assessment of the political economy of decarbonization efforts in Germany. The paradigm shift in Germany focuses mainly on a comprehensive energy transition that is also known as Energiewende. This narrative will demonstrate the complexity of policy measures undertaken, assess their effectiveness and bottlenecks as well as emerging conflicting targets and will include a discussion of intended solutions and future challenges.
urn:nbn:de:0084-diwkompakt_2015-0933
Keywords: 330